A jack of all trades is a master of none: the nexus of firm-specific Human capital, ambidexterity, productivity and firm performance - Kengatharan, N. (Sage Publishing Limited, 2020)
Drawing on the knowledge-based theory of the firm and organizational learning theory, the present study chiefly examines the impact of firm-specific human capital on organizational ambidexterity and the subsequent effect of organizational ambidexterity on productivity by integrating human capital theory with the theory of transaction cost. The data were garnered from 197 managers in Sri Lanka with self-reported questionnaires in a time-lagged approach. The results disclose strong significant relationships between the variables investigated: a chain of positive relationships between firm-specific human capital and organizational ambidexterity, organizational ambidexterity and productivity, and productivity and firm performance; and mediated relationships between firm-specific human capital and productivity through organizational ambidexterity, and between organizational ambidexterity and firm performance via productivity. The findings of the study push back the frontiers of human resource management literature in many ways. Notably, managers should be cognizant of the effects of firm-specific human capital, organizational ambidexterity, and productivity on firm performance.
Keywords: Firm-specific human capital; Organizational ambidexterity; Productivity; Firm performance; Knowledge-based theory of the firm